ANALISIS KAPASITAS BEBAN POLUTAN RUAS HILIR SUNGAI CITARUM MENGGUNAKAN QUAL2KW - Ayu Widya Utami; Pramiati Purwaningrum; Diana Irvindiaty Hendrawan (ITB Journal Publisher, LPPM ITB, 2020)
Abstract. The downstream segment of Citarum River flows from Bendung Curug, Karawang Regency and ends at Muara Gembong, Bekasi Regency. The pollution of downstream segment of Citarum River is caused by settlement, agriculture, farm, and industrial activities that dump their waste into river bodies. This causes a decrease in water quality and reduce the carrying capacity of the downstream segment of Citarum River pollutant. The purpose of this research was to analyze the pollutant load capacity (PLC) in downstream segment of Citarum River using QUAL2Kw model. This research was carried out downstream of Citarum River from segments 16 to 20 which were divided into 9 sections with 11 locations monitoring water quality. Sampling was carried out for 3 periods of observation that the sampling is done twice at each location using grab sampling method. Water quality parameters being modeled are BOD, COD, nitrate, and phosphate. The results of the simulation model of PLC for BOD was 14556.67 kg/day-23456.84 kg/day, COD was 24261.12 kg/day-39094.73 kg/day, nitrate was 24261.12 kg/day-39094.73 kg/day, and phosphate was 485.22 kg/day-781.89 kg/day. Overload of BOD was 0%-26%, COD was 61%-68%, phosphate was 78%-7%. Meanwhile, nitrate load in the Citarum River downstream segment doesn't exceed its pollutant load capacity. Keywords: Pollution Load Capacity, carrying capacity, Citarum River, Qual2Kw, water quality